Adjusting to Changing Environments: Virtual Preseason SCAT5 Assessment in Canadian Male Youth Football Players. Issue 2 (8th March 2023) - Syrydiuk, Reid A.; Penner, Linden C.; Sick, Stacy; Eliason, Paul; Galarneau, Jean-Michel; Leggett, Benjamin; Galea, Olivia; Schneider, Kathryn J.; Emery, Carolyn A.
Abstract : Objective: To provide preseason reference scores for Canadian youth tackle football players on the Sport Concussion Assessment Tool 5 (SCAT5) and to examine whether age, concussion history, and self-reported medical diagnoses are associated with SCAT5 subcomponent performance. Design: Cross-sectional study. Setting: Calgary, Alberta. Participants: Five hundred one male youth football players (ages 13-18 years) participating in the 2021 season. Assessment of Risk Factors: SCAT5 subcomponents were assessed by age group (13-14, 15-16, 17-18), concussion history (0, 1, 2+, and yes/no), and self-reported diagnoses (headache disorder, attention-deficit/hyperactive disorder, learning disability/dyslexia, and depression, anxiety, or other psychiatric disorder). Main Outcome Measures: Virtual video administration (vs traditional in-person testing) of the SCAT5 was completed, and subcomponent scores included total number of symptoms (/22), symptom-severity score (/132), Standardized Assessment of Concussion [orientation (/5), immediate memory (/30), concentration (/5), delayed recall (/10)], and modified Balance Error Scoring System (/30). Kruskal–Wallis, one-way analysis of variance, Mann–Whitney U, or independent t tests were used to assess possible associations depending on number of groups and data normality. Results: Virtual SCAT5 assessment scores across all outcomes did not differ by age group or concussion history. The median number of symptoms and median symptom-severity score at baseline was 2, and 173 players (34.5%) reported no symptoms. Median total number of errors on the modified Balance Error Scoring System was 3. Participants with certain self-reported diagnoses (attention-deficit/hyperactive disorder, dyslexia) demonstrated poorer performance on some SCAT5 subcomponents (symptom reporting, Standardized Assessment of Concussion). Conclusions: Baseline SCAT5 performance did not differ by age group or concussion history in male youth football players. Diagnoses of the self-reported disorders examined may be important considerations for interpretation of the SCAT5 assessment.